Bone marrow macrophage M2 polarization and adipose‐derived stem cells osteogenic differentiation synergistically promote rehabilitation of bone damage. Issue 12 (24th July 2019) - Li, Yiyang; Kong, Ning; Li, Zhe; Tian, Run; Liu, Xiaohui; Liu, Guanzhi; Wang, Kunzheng; Yang, Pei
Abstract: By differentiating into and the balance being regulated between M1 (pro‐inflammatory) and M2 (anti‐inflammatory) heterogeneous populations, macrophages play critical roles during the host immune response in various physiological contexts in both health and diseases. Besides regulating innate and adaptive immune capacity, macrophages are also decisively involved in tissue homeostasis. However, how resident macrophages are regulated after tissue damages is still far from elucidation. In the present study, we found that adipose‐derived stem cells (ADSCs) apparently promote bone defect rehabilitation in vivo via skewing differentiation of bone marrow–derived macrophage (BMDMs) towards anti‐inflammatory M2 macrophages. In vitro data demonstrated that although ADSCs have the potential to differentiate to osteoblasts and adipose cells by using standard tissue culture‐differentiating conditions, these mesenchymal progenitors are mainly regulated to differentiate into osteoblasts with overexpressed runt‐related transcription factor 2, osteoprotegerin, osterix, and downregulated receptor activator of nuclear factor κB ligand in the presence of BMDMs‐conditioned medium. Whereas BMDMs are polarized toward M2 macrophages with higher levels of arginase 1 and mannose receptor, but lower levels of inducible nitric oxide synthase and tumor necrosis factor‐α when cocultured with ADSCs. In short, all these findings collectively demonstrated that ADSCs and resident host cells can synergistically contribute to the bony repair through mutual regulation of their differentiation and cytokine secretion. Abstract : ADSCs promote macrophages to transfer M2 phenotype and M2 polarization. M2 polarization further enhances osteogenic differentiation of ADSCs. This mutual regulation may involve in rehabilitation of bone damage